Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika dengan Menggunakan Model Problem Solving di Sekolah Dasar - Arrahim Arrahim; Rika Sabrina (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research is motivated by the low ability to solve mathematical problems in fifth grade students of SDN Kaliabang Tengah 1 Bekasi Utara. Seen when researchers provide exercises in the description of mathematical problems in the form of stories on fraction material. There is still a lack of student knowledge regarding fractional material. When working on the story problem students simply add up or subtract the denominator by the denominator and the numerator by the numerator, without first equating the denominator. Students have not been able to solve problems correctly and many are still wrong. The lack of students' ability to infer results obtained from mathematical story problems. Enthusiastic students are lacking in solving mathematical story problems that are considered difficult. This study aims to improve the ability to solve mathematical problems using problem solving models in fifth grade students at SDN Kaliabang Tengah 1, North Bekasi. The research method uses Classroom Action Research (CAR) which consists of 3 cycles.. The conclusion of this study is the problem solving model can improve the ability to solve mathematical problems in fifth grade students at SDN Kaliabang Tengah 1 Bekasi Utara.